Rasagiline and Rapid Symptomatic Motor Effect in Parkinson’s Disease: Review of Literature - Pistacchi, Michele (Neurol Ther, 2013)
Rasagiline is a monoamine oxidase type-B inhibitor used as monotherapy or in addition to levodopa in the treatment of Parkinson’s disease. Once daily administration of rasagiline makes it easy to use, and allows good compliance by patients and adherence to therapy. Several multicenter studies have noted the effectiveness of rasagiline on both motor and non-motor symptoms, which require a complex pharmacologic approach, such as cognitive disorders. A recent study also reported a rapid action of rasagiline on motor symptoms. Positive findings have been highlighted by an economic model study. This review analyzes the main studies of rasagiline, with particular attention to the effectiveness of the drug on motor symptoms. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40120-013-0014-1) contains supplementary material, which is available to authorized users.